(untitled) (Tanzania Medical Journal, 2007)
Objectives: To assess the nutrition status among school age children in a rural community. Design: A cross sectional anthropometric survey. Setting: Mpwawa rural district, Central Tanzania. Methods: 639 children from ten randomly selected primary schools and 195 out-of-school children living close to the selected schools were included in the survey. Nutrition status was assessed using anthropometric indicators of Body Mass Index-for-age (BMI-for-age), weight-for-age (wt/age) and height-for age (ht/age). Results: A total of 834 children were included in the assessment. Their ages ranged from 7-18 years; 47.2% were males and 52.8% were females. The prevalence of thinness (BMI-for-age